1993
DOI: 10.1095/biolreprod49.3.515
|View full text |Cite
|
Sign up to set email alerts
|

Semen Characteristics, Testicular Size, and Reproductive Hormone Concentrations in Mature Duroc, Meishan, Fengjing, and Minzhu Boars1

Abstract: Chinese breeds of swine are known for their reproductive prolificacy and are noted for large litter size. The current investigation evaluated reproductive components of three breeds of Chinese boars in comparison to a contemporary site breed common in the U.S. Semen from postpubertal Duroc, Meishan, Fengjing, and Minzhu boars was collected during four seasons of the year. After each semen collection and evaluation period, boars were weighted and placed in a restraining chute for testicular measurements and blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
56
3

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(64 citation statements)
references
References 25 publications
5
56
3
Order By: Relevance
“…Heterosis may result in an increase in testicular mass, affecting the number of spermatozoa produced (Smital, 2009). However, a negative relationship between testis mass and number of spermatozoa has also been reported (Borg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterosis may result in an increase in testicular mass, affecting the number of spermatozoa produced (Smital, 2009). However, a negative relationship between testis mass and number of spermatozoa has also been reported (Borg et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Temperature and photoperiod show the most important effects on pigs (Kozdrowski and Dubiel, 2004;Rivera et al, 2005). It is suggested that photoperiod may play an important role, especially in temperate climates, due to the significant differences in day length over the year (Kunavongkrit et al, 2005 Sperm volume and concentration are lowest in the spring; they gradually increase during the summer, and reach a peak in late autumn (Trudeau and Sanford, 1986;Borg et al, 1993;Kozdrowski and Dubiel, 2004). Changes in the photoperiod cause variations in semen production (Mazzarri et al, 1970) and volume, and spermatozoa abnormalities (Sancho et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Meishan sows have also been reported to have higher levels of estradiol-17β, progesterone and inhibin than European sows [5]. However, the plasma concentrations of inhibin in Meishan boars have been shown to be lower than in European breeds [4,12].…”
Section: Discussionmentioning
confidence: 99%
“…novel because there is currently only data available for adults [4,12]. A negative correlation between inhibin and age has been reported in boys, bulls, and rats [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of quality and economics is limited by the number of insemination doses that can be obtained from one ejaculate and the number of appropriate quality ejaculates that can be obtained from a boar per week. Sperm production and its quality are influenced by many environmental factors such as the season (Love et al 1993;Ciereszko et al 2000;Corcuera et al 2002), breed (Borg et al 1993), age (Swierstra 1973), photoperiod (Sancho et al 2004;Andersson et al 1998), ambient temperature (Corcuera et al 2002), food intake (Kemp et al 1988), breed and testis size (Colenbrander et al 1990;Colenbrander et al 1993). One of the most important factors is the collection frequency, which determines both quantity and quality of sperm and, presumably, the number of spermatozoa in the ejaculate (Swierstra and Dyck 1976).…”
mentioning
confidence: 99%